2008
DOI: 10.1097/brs.0b013e318178e5ea
|View full text |Cite
|
Sign up to set email alerts
|

TNF-Alpha in Nucleus Pulposus Induces Sensory Nerve Growth

Abstract: Within the set of fluoro-gold-labeled neurons, 10% were positive for GAP43 in sham-operated animals, 22% positive in the TNF-deficient NP group, and 38% positive in the wild-type NP group. These intergroup differences in the percentage of GAP43-positive neurons were statistically significant (sham vs. TNF-deficient NP group: P = 0.009; TNF-deficient NP group vs wild-type NP group: P = 0.026). CONCLUSION.: The percentage of fluoro-gold-labeled GAP43-immunoreactive neurons significantly increased after injection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…There is accumulating evidence that IL-1β is capable of upregulating zinc-based matrix degrading enzymes, in particular matrix metalloproteinases, disintegrins, and metalloproteinases with thrombospondin motif, which may lead to degradation of collagen II and proteoglycan, as a result of losing ECM and severely reducing the ability of the NP to retain water 26 . TNF-α has been implicated in disc herniation and nerve root pain 27 . Teixeira et al showed a new therapeutic method for IVD degeneration by diclofenac-nanoparticles intradiscal injection, based on the modulation of inflammation 28 .…”
Section: Discussionmentioning
confidence: 99%
“…There is accumulating evidence that IL-1β is capable of upregulating zinc-based matrix degrading enzymes, in particular matrix metalloproteinases, disintegrins, and metalloproteinases with thrombospondin motif, which may lead to degradation of collagen II and proteoglycan, as a result of losing ECM and severely reducing the ability of the NP to retain water 26 . TNF-α has been implicated in disc herniation and nerve root pain 27 . Teixeira et al showed a new therapeutic method for IVD degeneration by diclofenac-nanoparticles intradiscal injection, based on the modulation of inflammation 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Homeostatic TNFSF/TNFRSF expression in the brain of mammals appears to be important for multiple neurological functions, including promoting nerve growth (Hayashi et al, 2008; Mi, 2008), differentiation (Hou et al, 2008), innervations (O’Keeffe et al, 2008), sensitization (Czeschik et al, 2008), and dendrite formation (Shao et al, 2005), and is supported by several streams of evidence. Firstly, TNFSF/TNFRSF expression occurs in the normal brain of the fetus, neonate, adolescent and adult mammal in developmentally regulated patterns and does not appear to induce neurological disease or inflammation (Twohig et al, 2010).…”
Section: The Neurological Expression Of the Tnfsf/tnfrsf Proteins Is mentioning
confidence: 96%
“…Secreted proinflammatory mediators include TNF-α, IL-1 α/β, IL-6, IL-17, IL-8, IL-2, IL-4, IL-10, IFN-γ, chemokines, prostaglandin (PGE)2, of these TNF-α and IL-1β are probably the most studied 2024 . TNF-α has been implicated in disc herniation and nerve irritation and ingrowth 25,26 , while both TNF-α and IL-1β induce upregulation of genes encoding matrix-degrading enzymes 20,27,28 . It has been demonstrated that expression of IL-1β and IL-1R are increased in degenerated disc tissue 20,21 .…”
Section: Introductionmentioning
confidence: 99%